Intervarsity Language Match 20232023 / Muhammad Aiman Abdul Halim, Dr. Nur Ilianis Adnan and Dr. Nur Husna Serip Mohamad - Abdul Halim, Muhammad Aiman; Adnan, Nur Ilianis; Serip Mohamad, Nur Husna (Academy of Language Studies, 2024)
The 'Intervarsity Language Match 2023' marked a collaborative effort by the English Language Club of UiTM Cawangan Pulau Pinang (UiTMCPP), together with Akademi Pengajian Bahasa (APB UiTMCPP) and Universiti Kuala Lumpur –Malaysian Spanish Institute (UniKL MSI). Themed 'English Unites Us,' this lively competition fostered student creativity and talent, showcasing linguistic prowess from both institutions. Simultaneously, it aimed to forge connections among students and educators, fortifying the bond between APB UiTMCPP and UniKL MSI. Students from both universities were given the opportunity to participate in three competitions, namely: • Intervarsity Scrabble Championship • Reimagined Tales: The Story Remix Challenge • Motivational Serenade In the Intervarsity Scrabble Championship, 32 participants (16 from UiTMCPP and 16 from UniKL MSI) engaged in a knockout-style Scrabble contest. The top two winners from each round advanced to face new opponents, starting within their university cohorts. As rounds progressed, the numbers decreased, culminating in a showdown between the finest two Scrabble players from UiTMCPP and UniKL MSI for the championship title. For the Reimagined Tales: The Story Remix Challenge, participants ingeniously fused two popular stories into one, demonstrating their adaptability and creativity. They could modify characters and plots, introducing a fresh and unexpected twist while focusing on uplifting themes of resilience, hope, and determination to spread positivity. In the Motivational Serenade, individuals or pairs modified well-known songs by rewriting lyrics with motivational themes, aiming to spread optimism. This creative endeavour not only showcased talent but also provided a platform to inspire and spread positive vibes among both participants and the audience.